2015
DOI: 10.1038/mi.2014.126
|View full text |Cite
|
Sign up to set email alerts
|

Thymic stromal lymphopoietin (TSLP) secretion from human nasal epithelium is a function of TSLP genotype

Abstract: Recent candidate gene and genome-wide association studies have identified "protective" associations between the single-nucleotide polymorphism (SNP) rs1837253 in the TSLP gene and risk for allergy, asthma, and airway hyperresponsiveness. The absence of linkage disequilibrium of rs1837253 with other SNPs in the region suggests it is likely a causal polymorphism for these associations, having functional consequences. We hypothesized that rs1837253 genotype would influence TSLP secretion from mucosal surfaces. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 53 publications
(89 reference statements)
2
25
0
1
Order By: Relevance
“…This indicates that the T allele is associated with decreased production of TSLP protein. Additionally, TSLP protein was decreased in non‐asthmatic individuals compared with asthmatic subjects, reinforcing the existing literature about the involvement of TSLP in asthma development . Our protein assay was not designed to detect the different isoforms of TSLP; validation at the protein level of our gene expression results, which showed differences between the short and long isoform of TSLP, is warranted.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…This indicates that the T allele is associated with decreased production of TSLP protein. Additionally, TSLP protein was decreased in non‐asthmatic individuals compared with asthmatic subjects, reinforcing the existing literature about the involvement of TSLP in asthma development . Our protein assay was not designed to detect the different isoforms of TSLP; validation at the protein level of our gene expression results, which showed differences between the short and long isoform of TSLP, is warranted.…”
Section: Discussionsupporting
confidence: 68%
“…NECs were expanded and cultured as previously described by Muller et al with some modifications. Poly(I:C) stimulation was performed as previously described by Hui et al RNA was extracted from the NECs using RNeasy Mini Kit (Qiagen) according to the manufacturer's instructions. The samples were reverse‐transcribed using iScript cDNA synthesis kit (Bio‐Rad) according to the manufacturer's instructions, and complementary DNA samples were aliquoted and stored at −80°C TSLP gene expression was assessed using SsoAdvanced™ Universal® SYBR Green Supermix (Bio‐Rad) with a MX4000 Stratagene detection system according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazilians, the A allele of IL1RL1 rs1041973 was positively associated with IL‐5 production and Ig E levels; expression quantitative trait loci analysis also suggested that polymorphism regulated the expression of the IL1RL1 gene via amino acid substitution . TSLP SNP rs1837253 showed correlation with TSLP protein secretion in human nasal epithelium but not with TSLP mRNA levels . In recent years, a new technology called Hi‐C has been widely applied by researchers worldwide to reveal various epigenomic mechanisms of various diseases.…”
Section: Discussionmentioning
confidence: 99%